Value Co-Creation Strategy Formulation for Tusuk Coffee to Enhance Customer Experience and Satisfaction - Muhammad Rizky Ridhani; Sonny Rustuadi (Publikasi Indonesia, 2024)
The research intends to identify Tusuk Coffee's issues, investigate the possible benefits of value co-creation as a strategic response, and make practical recommendations based on the findings. The study takes a mixed-methods strategy that combines exploratory and confirmatory research techniques. The data from this study were collected using two types of data: primary and secondary data. The primary data was collected using qualitative methods to be conducted with semi-structured interviews with 22 respondents through one-on-one interviews. Data analysis is carried out using qualitative data obtained from in-depth interviews as part of an exploratory phase to gather responses from customers. Subsequently, confirmatory analysis is conducted involving internal stakeholders, suppliers, and experts. The analysis employs thematic analysis, a method well-suited for various research designs. Using the 4P Marketing Mix model and the Value Co-Creation Canvas, the study assesses Tusuk Coffee's present strategies and suggests a customer-centric approach to value creation. The 4P Marketing Mix model was used to examine product, price, place, and promotion strategies. Value co-creation canvas creates a strategy that develops and delivers value by engaging deeply with its customers focusing on nine key areas: value proposition, company capabilities, company resources, the customer's job to be done, the customer's journey, the customer's resources, the customer's desired outcomes, the company's